9/5-(-11)/3-4/5+8/3 tính nhanh
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


1+2+3+4+5+6+7+8+9+10+11+12+13-1-2-3-4-5-6-7-8-9-10-11-12
=(1-1)+(2-2)+(3-3)+(4-4)+(5-5)+(6-6)+(7-7)+(8-8)+(9-9)+(10-10)+(11-11)+(12-12)+13
= 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 13
= 13
1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 + 12 + 13 - 1 - 2 - 3 - 4 - 5 - 6 - 7- 8 - 9 - 10
= (1+12) + (2+11) + (3+10) + ( 4+9) + (5+8) + (6+7) + 13 - (1+11) - ( 2+10) - ( 3+9) - (4+8) - (5+7) + 6 + 12
= 13 * 7 - 12 * 6 + 6
= 13
Ai k mk mk k lại

a: =-1/3+1/3=0
b: \(=\dfrac{4}{11}\left(-\dfrac{2}{7}-\dfrac{4}{7}-\dfrac{1}{7}\right)=\dfrac{4}{11}\cdot\left(-1\right)=-\dfrac{4}{11}\)
c: \(=10+\dfrac{5}{9}-3-\dfrac{5}{7}-4-\dfrac{5}{9}=3-\dfrac{5}{7}=\dfrac{16}{7}\)
d: \(=\dfrac{1}{3}+\dfrac{7}{4}-\dfrac{7}{4}+\dfrac{4}{5}=\dfrac{1}{3}+\dfrac{4}{5}=\dfrac{5+12}{15}=\dfrac{17}{15}\)
a: =-1/3+1/3=0
b: =411(−27−47−17)=411⋅(−1)=−411=411(−27−47−17)=411⋅(−1)=−411
c: =10+59−3−57−4−59=3−57=167=10+59−3−57−4−59=3−57=167
d: =13+74−74+45=13+45=5+1215=1715

A=(2+3+...+13)-(1+2+...+12)=2+3+...+13-1-2-...-12=(13-1)+(2-2)+(3-3)+...+(12-12)=12

a) 5 – 4 – 3 – 2 – 1 + 11 + 12 + 13 + 14 + 15
= (5 + 15) + (14 – 4) + (13 – 3) + (12 – 2) + (11 – 1)
= 20 + 10 + 10 + 10 + 10
= 60
b) 1 – 2 + 3 – 4 + 5 – 6 + 7 – 8 + 9 – 10 +11
= (1 + 3 + 5 + 7 + 9 + 11) – 2 – 4 – 8 – 10
= 36 – 24
= 12

a) 5 – 4 – 3 – 2 – 1 + 11 + 12 + 13 + 14 + 15
= (5 + 15) + (14 – 4) + (13 – 3) + (12 – 2) + (11 – 1)
= 20 + 10 + 10 + 10 + 10
= 60
b) 1 – 2 + 3 – 4 + 5 – 6 + 7 – 8 + 9 – 10 +11
= (1 + 3 + 5 + 7 + 9 + 11) – 2 – 4 – 8 – 10
= 36 – 24
= 12

B=4*13/9*3-4/3*40/9
B=4/3*13/9-4/3*40/9
B=4/3*(13/9-40/9)
B=4/3*(-27)/9
B=4*(-3)/9
B=-4
A=6/7 + 1/7.(2/7+5/7)
A=6/7 + 1/7.7/7=6/7+1/7.1
A=6/7+1/7=7/7=1

b: \(B=\dfrac{5}{2}-\dfrac{7}{2}+\dfrac{3}{8}+\dfrac{6}{8}+\dfrac{-6}{11}-\dfrac{5}{11}=-2-1+\dfrac{9}{8}=\dfrac{9}{8}-3=-\dfrac{15}{8}\)
c: \(C=\left(\dfrac{4}{3}+\dfrac{7}{3}+\dfrac{1}{3}\right)+\left(\dfrac{2}{5}+\dfrac{3}{5}\right)=4+1=5\)
d: \(D=\dfrac{4}{19}\left(\dfrac{-5}{6}-\dfrac{7}{12}\right)-\dfrac{40}{57}\)
\(=\dfrac{4}{19}\cdot\dfrac{-17}{12}-\dfrac{40}{57}=-1\)
e: \(E=\dfrac{1}{3}\left(\dfrac{4}{5}-\dfrac{9}{5}\right)+\dfrac{2}{3}=\dfrac{2}{3}-\dfrac{1}{3}=\dfrac{1}{3}\)

\(3+4+5+6+7+8+9+10+11\)
\(=\left(11+3\right)+\left(10+4\right)+\left(9+5\right)+\left(8+6\right)+7\)
\(=14+14+14+14+7\)
\(=63\)

=(9/5-4/5)-(11/3-8/3) =5/5-3/3 =1-1 =0 dễ vậy mà không biết :/